2019
DOI: 10.1039/c9cp01342c
|View full text |Cite
|
Sign up to set email alerts
|

Determining the gas composition for the growth of BNNTs using a thermodynamic approach

Abstract: A high-yield production of high-quality boron-nitride nanotubes (BNNTs) was reported recently in several publications. A boron-rich material is evaporated by a laser or plasma in a nitrogen-rich atmosphere to supply precursor gaseous species for nucleation and growth of BNNTs. Either hydrogen was added or pressure was increased in the system to achieve high yield and high purity of the synthesized nanotubes. According to the widely-accepted "root grow" mechanism, upon the gas cooling, boron droplets form first… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 83 publications
0
9
1
Order By: Relevance
“…In all cases, both atomic B (249.7 nm) and H (H α and H β at 656.2 and 486.1 nm, respectively) lines 46 were observed along with molecular emission bands from the BH (A 1 Π − X 1 ∑, (0,0) and (1,1) bands at 433.1 nm and 436.7) and NH (A 3 Π − X 3 ∑, (0,0) and (1,1) bands at 336.0 and 337.0 nm) radicals, 47 which are known as good BN precursors. 25,48 Their intensities vary with plasma power, as their concentrations strongly depend on the plasma temperature. As the input power decreases, the intensity of the atomic B line decreases rapidly, as indicated in Figure 6e (in a dotted circle), which implies insufficient B vapor generation due to the poor evaporation of feedstock or rapid B droplet formation due to faster cooling of the plasma jet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all cases, both atomic B (249.7 nm) and H (H α and H β at 656.2 and 486.1 nm, respectively) lines 46 were observed along with molecular emission bands from the BH (A 1 Π − X 1 ∑, (0,0) and (1,1) bands at 433.1 nm and 436.7) and NH (A 3 Π − X 3 ∑, (0,0) and (1,1) bands at 336.0 and 337.0 nm) radicals, 47 which are known as good BN precursors. 25,48 Their intensities vary with plasma power, as their concentrations strongly depend on the plasma temperature. As the input power decreases, the intensity of the atomic B line decreases rapidly, as indicated in Figure 6e (in a dotted circle), which implies insufficient B vapor generation due to the poor evaporation of feedstock or rapid B droplet formation due to faster cooling of the plasma jet.…”
Section: Resultsmentioning
confidence: 99%
“…As the input power decreases, the intensity of the atomic B line decreases rapidly, as indicated in Figure e (in a dotted circle), which implies insufficient B vapor generation due to the poor evaporation of feedstock or rapid B droplet formation due to faster cooling of the plasma jet. The nucleation of B droplets from their vapors occurs at 4200 K. , The OES measurement clearly shows that the thermofluid fields are largely affected by the plasma power and thus are studied in detail by numerical simulations.…”
Section: Resultsmentioning
confidence: 99%
“…A scarce amount of fibrous-like BN assemblies can be seen to form on the small boron particles. When the temperature of the B/N gas mixture drops below the boron vaporization point, the system becomes oversaturated with respect to boron partial pressure [83] leading to condensation of boron into the small droplets. This leads to a decrease of the concentration of atomic boron in the gas phase.…”
Section: Bnns From Boron Powder Precursormentioning
confidence: 99%
“…36,37 The results showed that for B-N and B-N-H gas mixtures under thermodynamic equilibrium at pressures 1-10 atm and gas temperatures of T g <4000 K, B 2 N molecules dominate and their density outnumber BN molecules by 2-3 orders of magnitude. 36 In addition, this work presented also the first experimental documentation of the emission by excited B 2 N molecules in the visible spectrum, which was recorded in the laser ablation plume from a solid BN target. In the present paper, we are going beyond these initial studies of laser ablation of solid BN targets and focus on a comparison of gas phase reactions in the ablation plumes from boron and boron nitride targets.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study of the gas composition for high temperature growth of BN nanomaterials, 36 the formation of different chemical species relies on using the thermodynamic approach of minimization of the Gibbs free energy. 36,37 The results showed that for B-N and B-N-H gas mixtures under thermodynamic equilibrium at pressures 1-10 atm and gas temperatures of T g <4000 K, B 2 N molecules dominate and their density outnumber BN molecules by 2-3 orders of magnitude. 36 In addition, this work presented also the first experimental documentation of the emission by excited B 2 N molecules in the visible spectrum, which was recorded in the laser ablation plume from a solid BN target.…”
Section: Introductionmentioning
confidence: 99%